Virtual Legal Culture That Hinders the Rights of Statutory Rape Victim Girls to Receive Protection and Recovery - Ni'mah, Zulfatun (Martabat: Jurnal Perempuan dan Anak, 2024)
A girl who engages in sexual intercourse with an adult man is legally considered a victim of sexual violence in the form of statutory rape, thus entitled to protection and recovery. However, in a statutory rape case involving a teacher and student in Gorontalo in September 2024, the victim's identity was widely disseminated online, complicating the protection and recovery process. This research aims to identify the virtual legal culture that undermines the rights of female victims of statutory rape to receive protection and recovery. The study employs an ethnographic method with a socio-legal approach. Data were collected through virtual observation of TikTok accounts responding to statutory rape cases in Gorontalo and analyzed using content analysis techniques. The results show a series of legal cultures that hinder the fulfillment of the rights of female statutory rape victims to enjoy protection. These include the "kepo" culture, or excessive curiosity about others' affairs, which drives the public to delve deeply into the case; the "social climbing" culture, where individuals exploit the case's popularity to boost their notoriety; and the "spill the tea" culture, or online gossiping, used as a form of social sanction against the girl, who is often wrongly perceived as the perpetrator of adultery.